Beyond Decibels: Spectral and Perceptual Dichotomy of Noise in a Busy Emergency Department (ED) - Wang, Guangxing; Zhang, Nuowei; Lin, Houlai (Archives of Acoustics, 2026)
This study investigates the acoustic environment of a high-volume emergency department in a Chinese tertiary hospital and its differentiated perceptual impacts on occupants. Continuous 24-h monitoring was conducted for 20 consecutive days in four representative areas: triage, waiting area, treatment rooms, and bridge. Daily 24-h LAmin, LAeq, and LAmax were analyzed, and one-third-octave band sound pressure levels were used to identify dominant frequency components. Structured questionnaires were administered to healthcare staff, patients, and visitors to assess subjective noise perception and psychological responses. Objective measurements showed severe and persistent noise pollution. Mean LAeq ranged from 62.2 dB(A) in treatment rooms to 67.0 dB(A) on the bridge. The triage showed the highest background noise (LAmin = 52.8 dB(A)), whereas the bridge exhibited the highest peak level (LAmax = 82.3 dB(A)). Diurnal analysis revealed a sustained daytime high-noise plateau in all areas, and nighttime levels remained well above recommended limits. Spectral analysis showed a pronounced peak around 500 Hz, indicating that human speech was strongly associated with the ED soundscape. Perceptual results revealed a clear dichotomy: healthcare staff showed signs of cognitive adaptation, whereas patients and visitors responded more strongly through emotion-driven stress and communication-related discomfort. Piercing call bells and speech masking emerged as salient sources of disturbance for the public, while healthcare staff appeared more tolerant of routine operational sounds. These findings position noise in the ED as not only an acoustic burden but a human-factors challenge, underscoring the need for integrated interventions to improve communication, reduce stress, and advance safer, more patient-centered emergency care.